Perforated Ray Cells in Pistacia terebinthus - a New Record for Anacardiaceae - Agarwal, Manisha; Gupta, Sangeeta; Chauhan, Laxmi; Painuly, Veena (Indian Forester, 2002)
This paper reports perforated ray cells in the wood of Pistacia terebinthus of the family Anacardiaceae. In this species the perforated ray cells were found isolated , localized mainly on the ends of multiseriate rays. The perforated ray cells are larger than other ray cells , with simple perforation plate and bordered pits , as in vessel elements , located on radial walls.